Pendekatan SOAR Dalam Strategi Pengembangan Wisata SOAR dalam Strategi Pengembangan Wisata Kampung Lawas Maspati Kota Surabaya - Nisrinada Zahirahaini Fajrin; Ertien Rining Nawangsari (Universitas Musamus, Merauke, Papua, 2023)
The Tourism Village or Village is one of the flagship programs of the Ministry of Tourism and Creative Economy (Kemenparekraf) which is carried out as an effort to restore tourism during the COVID-19 pandemic. Kampung Lawas Maspati is one of the tourist villages that has cultural and historical values ​​for the Indonesian nation as well as various awards. Various tourism development activities have been carried out, however, the situation is not gradually improving. This study aims to determine the appropriate tourism development strategy in Kampung Lawas Maspati, Surabaya City. This research uses descriptive qualitative research method with SOAR analysis. The results show that the strength of Kampung Lawas Maspati is the existence of historical buildings. The opportunity that exists is that many people have businesses. The aspiration of the community is to mobilize UKM. The desired result is an increase in the economy. The appropriate strategy to be applied in Kampung Lawas Maspati is the SA and OR strategies. By implementing SA and OR strategies such as the existence of tour packages, the introduction of UKM and the collaboration that is carried out can increase the income of the village and the community as UKM actors. Meanwhile, through branding, tourists will be interested in visiting Kampung Lawas Maspati. This income will later help the community's economic recovery as well as better tourism development activities.